Successful containment of horizontal enterovirus infection in a neonatal unit in Singapore through diagnosis by polymerase chain reaction (PCR) and direct sequence analysis - Tan, Y.Y. (Elsevier Ltd, 2021)
10.1016/j.jiph.2020.06.029